RETRACTED: Pengaruh jumlah pohon, produktivitas dan upah pekerja penyadapan getah pinus terhadap penerimaan negara di Kabupaten Simalungun - Benteng H Sihombing; Tioner Purba (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
RETRACTED: Pengaruh jumlah pohon, produktivitas dan upah pekerja penyadapan getah pinus terhadap penerimaan negara di Kabupaten SimalungunSihombing, B. H., & Purba, T. (2023). Pengaruh jumlah pohon, produktivitas dan upah pekerja penyadapan getah pinus terhadap penerimaan negara di Kabupaten Simalungun. Jppi (Jurnal Penelitian Pendidikan Indonesia), 9(4), 205-214.Based on the author's request to change the affiliation from Universitas Lancang Kuning to Universitas Simalungun, made on September 6, 2024, this is not permissible as the journal has already been published for one year, and the author is only now requesting the change.The norm is to list the institution where the work was conducted and to indicate the new corresponding address or email in a footnote (or if there is already a footnote, the new affiliation/contact should immediately follow). It appears that minimal work (if any) was conducted at the new institution, so the affiliation should reflect where the work was originally done. Politically, the new institution may want to claim the new publication, and the author might want to assist with this. However, since the work was completed at the prior institution on their salary, the resulting article should maintain that affiliation, with a note providing the author’s new address.